1992
DOI: 10.1111/j.1365-3024.1992.tb00032.x
|View full text |Cite
|
Sign up to set email alerts
|

Potent immunosuppression by secretory/excretory products of larvae from the sheep blowfly Lucilia cuprina

Abstract: Secretory/excretory products (sec/ex) of parasitic larvae of the sheep blowfly Lucilia cuprina potently inhibited proliferation of peripheral blood leucocytes stimulated by mitogens in vitro. Suppression of proliferation was not due to irreversible damage because cells cultured for 24 h in high concentrations of sec/ex appeared viable (assessed by Trypan blue exclusion) and did not show impaired proliferation after washing. Furthermore, suppression induced by sec/ex could be overcome by increasing concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 11 publications
1
13
0
1
Order By: Relevance
“…The importance of ASMase for the development of ALI has been shown in many models such as pulmonary edema caused by PAF [Kerlin and East, 1992], lipopolysaccharide (LPS) [Claus et al 2005;Goggel et al 2004;Haimovitz-Friedman et al 1997], acid instillation [Goggel et al 2004] or repeated lung lavage [von Bismarck et al 2008]. Importantly, impairment of ASMase improved not only vascular barrier functions (as shown in all studies above), but also oxygenation [von Bismarck et al 2008;Goggel et al 2004].…”
Section: Smmentioning
confidence: 84%
“…The importance of ASMase for the development of ALI has been shown in many models such as pulmonary edema caused by PAF [Kerlin and East, 1992], lipopolysaccharide (LPS) [Claus et al 2005;Goggel et al 2004;Haimovitz-Friedman et al 1997], acid instillation [Goggel et al 2004] or repeated lung lavage [von Bismarck et al 2008]. Importantly, impairment of ASMase improved not only vascular barrier functions (as shown in all studies above), but also oxygenation [von Bismarck et al 2008;Goggel et al 2004].…”
Section: Smmentioning
confidence: 84%
“…Pruett (3) showed that Hypodermin A cleaves bovine IgG. In the same manner, Lucilia cuprina (Calliphoridae) larvae contain digestive tryptic and chymotryptic proteases involved in larval nutrition (4) and avoidment of cellular (5,6) and humoral immune responses, with cleavage of IgG (7–9). Moreover, excretion of ammonia by L. cuprina larvae suppresses immunity in sheep (10).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the sheep blowfly, the ability of the larvae to degrade host immunoglobulin (62) is one clear example whereby the larvae are capable of avoiding the host humoral immune response. In addition, excretory/secretory (E/S) products produced by the larvae have been shown to be able to directly influence the immune response at both the cellular and humoral levels (66). The results from this study demonstrated that the proliferation of ovine lymphocytes could be suppressed in vitro following exposure to the larval products, but interestingly this suppression could be reversed.…”
Section: Inhibitors Of Immune Control -Immunosuppressionmentioning
confidence: 72%